2010
DOI: 10.1038/mi.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasin (S100A7) is a major Escherichia coli-cidal factor of the female genital tract

Abstract: The female urogenital tract requires an efficient defense against bacteria, potentially derived from the adjacent intestinal tract. We have thus sought to identify the factors that protect against Escherichia coli (E. coli) in the female genital tract. Vaginal fluid from healthy human donors consistently killed E. coli in vitro and vaginal epithelium strongly expressed and secreted psoriasin. Psoriasin was constitutively produced in an organotypic vaginal epithelium model, and exposure of these cells to supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 31 publications
(28 reference statements)
2
35
2
2
Order By: Relevance
“…However, in vitro studies have shown that S100A7 has strong anti-Escherichia coli activity 38 and is expressed by epithelial cells when they are exposed to microbial products. 12 Furthermore, histones and RPS27A are known to have pivotal functions in the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies have shown that S100A7 has strong anti-Escherichia coli activity 38 and is expressed by epithelial cells when they are exposed to microbial products. 12 Furthermore, histones and RPS27A are known to have pivotal functions in the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…oxS100A7 is highly abundant on healthy human skin and several mucosal surfaces (11)(12)(13). Its antibacterial activity is Zn 2+ -sensitive, acting via a histidinecoordinated low-affinity Zn 2+ -binding site (14).…”
Section: Significancementioning
confidence: 99%
“…But the changes in the culture were not as impressive as in the native urine of the treated women. The locally applied lactic acid gel can also disturb the E.coli life cycle indirectly through changes of the vaginal environment [8], local innate immunity [9] or shift in the composition of the vaginal microbiota [10,11]. Filamentous transformation of E.coli was also reported as part of the life cycle of uropathogenic E.coli to subvert innate defenses of the host [12].…”
Section: Discussionmentioning
confidence: 98%